Morphological characterization of the hippocampus: a first database in Ecuador - Cevallos, Stefano Buitrón; Jerves, Alex X.; Vinueza, Clayreth; Hernandez, Dennis; Ávila, Carlos; Auquilla, Andrés; Alvear, Óscar (Frontiers in Human Neuroscience, 2024)
Introduction: the hippocampal volume is a well-known biomarker to detect and diagnose neurological, psychiatric, and psychological diseases. However, other morphological descriptors are not analyzed.Furthermore, not available databases, or studies, were found with information related to the hippocampal morphology from Latin-American patients living in the Andean highlands.Methods: the hippocampus is manually segmented by two medical imaging specialists on normal brain magnetic resonance images. Then, its morphological qualitative and quantitative descriptors (volume, sphericity, roundness, diameter, volume-surface ratio, and aspect ratio) are computed via 3D digital levelset-based mathematical representation. Furthermore, other morphological descriptors and their possible correlation with the hippocampal volume is analyzed.Results: we introduce a first database with the hippocampus' morphological characterization of 63 patients from Quito, Ecuador, male and female, aged between 18 and 95 years old.